Acute simultaneous multiple lacunar infarcts as the initial presentation of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy. Issue 7 (July 2015) - Hsiao, Cheng‐Tsung; Chen, Yun‐Chung; Liu, Yo‐Tsen; Soong, Bing‐Wen; Lee, Yi‐Chung
Abstract : Abstract : Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an adult‐onset, dominantly inherited small‐vessel disease of the brain caused by NOTCH3 mutations and characterized by recurrent subcortical infarctions, dementia, migraine with aura, and mood disturbance. We report a patient with unusual presentation of CADASIL with acute simultaneous multiple subcortical lacunar infarcts as the first manifestation. A 69‐year‐old man developed confusion, drowsiness, right hemiparesis, and slurred speech following orthopedic surgeries. Brain magnetic resonance imaging revealed diffuse leukoencephalopathy and multiple acute subcortical lacunar infarcts. Brain magnetic resonance angiography, echocardiography and 24‐hour electrocardiography were unremarkable. The symptoms improved quickly after treatment with fluid hydration and antiplatelet agent, and his consciousness and mentality totally recovered within 3 days. The NOTCH3 genetic testing showed a heterozygous missense mutation, c.1630C>T (p. Arg544Cys). The experience in this case suggests that brain imaging is important in managing postoperative confusion, and any patient with diffuse leukoencephalopathy of unknown etiology may need to be tested for NOTCH3 mutations. Surgery is an important factor of encephalopathy and acute infarction in individuals with NOTCH3 mutations. Comprehensive presurgical evaluations and proactive perioperative precautions to avoid dehydration and anemia are necessary for patients with CADASIL who are about to receive anesthesia and surgery.